Et utrykt stambogsdigt af Schack Staffeldt - Blicher, Henrik (Danske Studier, 2024)
Schack Staffeldt (1769-1826) studied at the Georg-August-Universität in Göttingen c. 1793. Recently the poems of Schack Staffeldt were collected in the three-volume publication Samlede digte (Copenhagen, 2001), but his poetic entry in the album of the Danish theologian Wolf Frederik Engelbreth, dated February 1793 in Göttingen, has not been known to the public until now. The article argues that the poem »Youth and Old Age« contributes to the portrait of the Danish poet in his formative years prior to Romanticism.